Implementation Application Alfred Camera as Media Supervision on Patrol Activities in Preventing Theft Crime at Legal Area of Sabang City - Riski Aulia (Police Studies Review, 2021)
The research was demand on an increase of theft cases in the Sabang City area due to low prevention action with patrol activities of Police Unit of Sabang city. The activities carried out by officers have been not optimally. This is due to the existence of culture on member patrols. to minimize the development of this old culture, a maximum leader supervision is required by the leadership of the performance on its members while in order to achieve optimal results with using application of Alfred Camera. Therefore, this research aims to identify how the Alfred camera application is implemented as a monitoring control for patrol activities and to find the affecting factors. This research use a theories and concepts as a analytical in research process. which is theory technology information, crime prevention theory, and management theory. While the concepts is Supervision consept, the Concept of Patrol and the Concept of the Alfred Camera. The type of method is a qualitative research with using techniques data, which is observation, interviews, and study document. Based on the result of research, the maximum supervision in implementation of patrol activities can improve the performance of members patrol and improve a optimal results when compared to the absence of supervision carried out. However, in the implementation of Alfred camera on patrol activities there are still inhibiting factors that affecting on members patrol such as the budget fund management and the condition of inventory items which will later support the smooth running of patrol activities more optimally.